Transient and transgenic approaches for functional testing of candidate genes in barley - Nagy, Bettina (Acta Biologica Szegediensis, 2011)
Barley represents one of the major crops grown worldwide. More than ten years have passed since the first stable Agrobacterium-mediated barley transformation was reported. Since then, several progresses have been made thanks to a number of technical improvements. As a result of our established barley transformation protocol, five different candidate genes were used for barley transformation. The transgenic lines were analyzed at biochemical and physiological levels. The aim of our work was to develop an effective and reproducible system for the analysis of transgenic lines (transient assay system in microprojectile bombarded barley leaf) which can be applied for testing the cellular stress response or cellular stress tolerance of the stable transgenic genotypes compared to the wild type barley. According to the results of the candidate gene testing in the transgenic lines, the investigated gene significantly increased the tolerance to the applied (drought) stress. Further experiments showed that these significant differences in the transient GFP/DsRed expression may correlate to the stress tolerance of the transgenic line.